The Interference of Online Texting Language in Essay Writing - Md Yunus, Melor; Hashim, Harwati; Aifa Norharmi, Alia; Izza Hazwani Rohizad, Nur; Safira Ibrahim, Izyan (International Journal of Engineering and Technology, 2018)
Communicating through text is no longer seen as something peculiar nowadays. In fact, those who are not familiar with this medium will be seen as an outlier. Interference is viewed as elements transference of one language into another language at various stages of linguistics such as phonology, morphology, syntax and the orthography of the languages.  Surprisingly, current studies have shown that the exposure to textese had effect on spelling.  Thus, this study aimed to find out whether textese has influenced students’ essay writing.  This study was participated by 67 Form 4 students of an academy at one of the states in Malaysia involving 27 males and 40 females. All respondents are regular users of text messaging.  Data collected were analysed using percentages.  From the findings, it can be concluded that online texting language usage in messaging platform affects students’ writing skills. Their responses showed that they use abbreviation in their writing and consciously do spelling mistakes. This phenomenon is alarming and certain measures should be taken into consideration in overcoming these issues.